2008
DOI: 10.2147/jpr.s3717
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal aerosolization of bupivacaine is a safe and effective method in controlling postoperative pain in laparoscopic Roux-en-Y gastric bypass

Abstract: IntroductionObesity is a worldwide problem and has grown in severity in the last few decades making bariatric surgery and, in particular, laparoscopic banding and Roux-en-Y gastric bypass efficacious and cost-effective procedures. The laparoscopic approach has been shown to offer significant healthcare benefits, of particular interests are reports of decreased postoperative pain resulting in a shorter hospital stay and an earlier return to normal activity. However, many patients still experience significant pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Five studies were suitable for meta‐analysis. These were in fundoplication20, 21, Roux‐en‐$\font\ss=cmss10 scaled 1000 \hbox{Y}$ bypass22, 23 and gastric banding24.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were suitable for meta‐analysis. These were in fundoplication20, 21, Roux‐en‐$\font\ss=cmss10 scaled 1000 \hbox{Y}$ bypass22, 23 and gastric banding24.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous recent randomized studies of bariatric patients handled with other strategies proposed to diminish postoperative pain such as bupivacaine pump systems, intraoperative or continuous intraperitoneal bupivacaine application, systemic lidocaine, ultrasound-guided transversus abdominis plane block, etc. [13,[25][26][27][28][29]. These studies render different results, not always reproducible by other authors and expensive to apply in clinical practice in some cases.…”
Section: Discussionmentioning
confidence: 96%
“…Symons et al achieved reduction in postoperative oral narcotic use, with no differences in pain scores or outcome variables between the groups [26]. Alkhamesi et al, in contrast, reported lower pain scores in the treatment group, while maintaining similar levels of postoperative rescue medication use [27]. A study by Cottam et al showed that continuous postoperative subfascial/subcutaneous infusion of bupivacaine via subcostal catheters allowed switching patientcontrolled meperidine to oral analgesics quicker in the treatment group while maintaining similar pain scores as in the control group [13].…”
Section: Discussionmentioning
confidence: 96%
“…It may be combined with pre-incision infiltration [165]. Efficacy of its use has also been demonstrated in bariatric surgery [166] and ropivacaine or levobupivacaine seem to be more effective than short-acting agents, like lidocaine [167]. Recently, it was reported that ultrasound-guided transversus abdominal plane block is feasible and safe in bariatric surgery [168] but data from RCTs comparing this technique with local anaesthetic infiltration are lacking.…”
Section: Postoperative Analgesiamentioning
confidence: 99%